Effects of Zn (II) on the Optical Properties of CdTe Quantum Dots and Their Photoluminescence Response to Lead Ion - Nhan, Nguyen Thi; Duc, Vu Anh; Dung, Mai Xuan; Bac, Hoang Quang (VNU Journal of Science: Natural Sciences and Technology, 2022)
Water-soluble CdTe quantum dots (QDs) have been utilized as photoluminescence probes for the detection of metal ions such as Pb 2+ , Hg 2+ , Cd 2+ , etc. We initially developed highly photoluminescence (PL) Zn-doped CdTe for toxic ions detection. A study on the changes of optical properties of Zn-doped CdTe and CdTe QDs when exposed to Pb 2+ suggested that Pb 2+ could act as a surface passivating agent to reduce Te 2- dangling bonds while Zn 2+ dopant stabilizes the QDs surface against ambient oxidation. The results demonstrated herein provide useful  understandings of the interactions between water-soluble QDs and metal ions. These results suggest further applications of QDs in sensing metal ions.